Contemporary Thai literary style in the period of Cold War: A Case study of Pramun Aunha-Thup’s literary works - Phongpheng, Vannaporn (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2019)
This study analyzes the characteristics that define the literary style pioneered by Pra-mun Aunha-thup, one of Thailand's greatest contemporary writers. His unconventional use of Thai grammar, combined with a style that seamlessly fused newspaper journalism and traditional descriptive writing together created a unique prose writing style that illuminates both hisconsiderable talents as a writer and the turbulent cold war period in Thailand in which he lived and worked. During this time, a period marked by great ideological differences, modernization, urbanization and industrialization in Thai society and the influence that the West brought to bear through Hollywood movies and translated literary works, Pra-mun Aunha-thup's literary style heralded the advent of Thai literature in a modern context.